Formulation, Development & Characterization of Gels of Extracts of Butea monosperma & Acacia arabica Linn. & Evaluation of Wound healing Activity - Shakya , Dinesh; Singh, Namrata (Journal of Neonatal Surgery, 2025)
The extracts were tested for acute oral and dermal toxicity studies on the basis of OECD guidelines. Normal healthy albino rats were chooses and grouped for the wound healing study. The excision, incision and dead space wounds were implicated on back side of albino rats. In excision wound model extracts were applied topically for 14 days. At the end of study Wound area, % wound closure and day of epitheliazation were calculated. In incision wound model all extracts were administered orally at a dose of 200 mg/kg body weight for 14 days. At the end of study tensile strength (Skin breaking strength) was measured with the help of tensiometer. In Dead Space wound model all extracts were administered orally at a dose of 200 mg/kg body weight for 14 days. At the end of treatment the wet and dry weight of granulation tissue, hydroxyproline content with % collagen and % elastin level were measured. Some antioxidant parameters like SOD, GSH, and Catalase and lipid per oxidation level also estimated in blood of rats of dead space wound model. Among all extracts ethanolic extract of bark of Acacia arabica and Butea monosperma were found to be most effective in management of delayed wound healing. The acute (Oral and Dermal) toxicity studies, excision, incision and dead space wound model were implicated for wound healing activity of ethanolic extract of Acacia arabica and Butea monosperma with all biophysical and biochemical parameter estimation same described above for examination of extract. On the basis of above investigations, it is concluded that the ethanolic extract of bark of Acacia arabica and Butea monosperma have effective role in treatment of delayed wound healing in normal albino rats